Synthesis and Characterization of Bio-Based Porous Carbons by Two Step Physical Activation with CO2 (Jurnal Teknologi (Sciences & Engineering), 2014)
Porous carbons were synthesized from coconut shell using two step CO2 activation and their characteristics were investigated. Nitrogen adsorption test for Brunauer-Emmett-Teller (BET) specific surface area and pore volume of the adsorbent produced were carried out. The Langmuir surface area, BET surface area and pore volume of the synthesized carbon are 533 m2/g, 361 m2/g and 0.19 cm3/g respectively. Micropores are predominant constituting 88% of the total surface area. From the Fourier Transform Infrared Spectroscopy (FTIR) analysis, hydroxyls, alkenes, carbonyls and aromatics functional groups were identified. Thermogravimetric analysis (TGA) results gives thermal analysis whereby moisture pyrolysis occurred at 105oC, the pyrolysis of hemicellulose and cellulose occurred at 160â€“390oC. However, lignin decomposition occurred in a wider temperature range (390-650oC). The proximate and ultimate analysis shows high percentage of carbon and less ash content which indicates a good precursor material for porous carbon.Â Â